Pidato para khalifah : persoalan negara, demokrasi, dan penegakan hukum / H. Abd Halim; editor, H. Abd Basyid, Taufiq Hakim - HALIM, ABD. H, 1963-; Basyid, Abd. H; Taufiq Hakim (INDES, 2015)
xiii, 218 hlm. ; 23 cm.